Association between overtime work hours and preventive dental visits among Japanese workers - Yoshikazu Harada; Tomohisa Nagata; Masako Nagata; Arisa Harada; Ryoichi Oya; Koji Mori (BMC, 2021)
Abstract Background This study aimed to examine the association between overtime work and the frequency of preventive dental visits among workers in Japan. Methods A self-administered questionnaire was completed by 14,847 daytime-workers. We used a logistic regression model stratified by sex and age and adjusted for marital status, occupation, education, and oral status to investigate the association between overtime work hours and the frequency of preventive dental visits. Results In total 1037 men (9.3%) and 511 women (13.9%) attended quarterly preventive dental visits, and 2672 men (23.9%) and 1165 women (31.8%) attended annual preventive dental visits. Overtime work was statistically significantly associated with quarterly preventive dental visits among men aged 50-59 years, with adjusted odds ratios (aOR) and 95% confidence intervals (CI) of 0.73 (0.56-0.95), 0.75 (0.54-1.04), and 0.55 (0.34-0.90) for < 20, 20-39, and ≥40 h overtime/month, respectively. No such trends were observed for men aged < 50 years and women of all ages. Overtime work of < 20, 20-40, and ≥40 h overtime/month was statistically significantly associated with annual preventive dental visits among men aged 40-49 years (aOR [95%CI]: 0.76 [0.61-0.95], 0.84 [0.65-1.09], and 0.72 [0.51-1.00], respectively) and 50-59 years (aOR [95%CI]: 0.75 [0.61-0.91], 0.76 [0.59-0.97], and 0.63 [0.45-0.88], respectively). No such trends were observed in men < 40 years and women of all ages. Conclusions Our study revealed associations between overtime and preventive dental visits among male workers aged in their 40s and 50s.